Seroprevalence of hepatitis B virus, hepatitis C virus and human immunodeficiency virus in the western region of Nepal - Shrestha, Umid Kumar; Bhatta, Bhup Dev (Journal of Advances in Internal Medicine, 2017)
Background and aims: The hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are associated with major public health concerns. The aim of the study was to determine the seroprevalence of HBV, HCV and HIV in the western region of Nepal.Methods: This was a cross-sectional observational study, in which 15,791 patients, attending to Manipal Teaching Hospital, Pokhara, Nepal, were investigated for HBV, HCV and HIV from June 2013 to March 2016; demographic and biochemical profile were studied among the patients with positive test results.Results: Among 15,791 patients [male 6614 (41.9%) and female 9177 (58.1%)], HBV was found in 180 (1.1%), HCV in 52 (0.3%) and HIV in 77 (0.5%). The HBV was found in 63.9% of males and 36.1% of females, HCV in 67.3% of males and 32.7% of females, and HIV in 61% of males and 39% of females which showed that males had more positivity of HBV (P